Biological response of pulps submitted to different capping materials - Briso, André Luiz Fraga [UNESP]; Rahal, Vanessa; Mestrener, Sandra Rahal[UNESP]; Dezan Junior, Eloi [UNESP] (FapUNIFESP (SciELO), 2006)
Pulp capping is a procedure that comprises adequate protection of the pulp tissue exposed to the oral environment, aiming at the preservation of its vitality and functions. This study evaluated the response of the dental pulps of dog teeth to capping with mineral trioxide aggregate (MTA) or calcium hydroxide P.A. For that purpose, 37 teeth were divided into two groups, according to the capping material employed. Two dogs were anesthetized and, after placement of a rubber dam, their pulps were exposed in a standardized manner and protected with the experimental capping materials. The cavities were then sealed with resin-modified glass ionomer cement and restored with composite resin. After sixty days, the animals were killed and the specimens were processed in order to be analyzed with optic microscopy. It was observed that MTA presented a higher success rate compared to calcium hydroxide, presenting a lower occurrence of infection and pulp necrosis.
Keywords: Biocompatible materials; Calcium hydroxide; Dental pulp capping; aluminum derivative; biomaterial; bone cement; calcium derivative; calcium hydroxide; mineral trioxide aggregate; oxide; resin; silicate; animal; dentin; disease model; dog; drug combination; drug effect; endodontics; methodology; nonparametric test; pathology; standard; tooth pulp; Aluminum Compounds; Animals; Biocompatible Materials; Bone Cements; Calcium Compounds; Calcium Hydroxide; Composite Resins; Dental Pulp; Dental Pulp Capping; Dental Pulp Exposure; Dentin; Disease Models, Animal; Dogs; Drug Combinations; Oxides; Pulpotomy; Silicates; Statistics, Nonparametric